Fuzzy Adaptive Finite-time Control of Stabilized Platform in Rotary Steerable System with Sensor and Actuator Failures - Wan, Min; Cen, Qi; Zhou, Lifang (Scientific Journal of Technology, 2026)
This paper investigates the tracking control problem of a stable platform with a rotating guidance system that has sensor and actuator failures. In order to improve the robustness of the angle control of rotary steering system drilling tools, a fuzzy adaptive finite-time control is proposed. Compared with existing control strategies, this paper integrates dynamic surface control technology and finite-time technology through adaptive fuzzy backstepping control to address the trajectory tracking problem of a rotating guidance system with simultaneous sensor and actuator failures. A fuzzy state observer is designed to observe unobservable states in the system. Then, based on the Lyapunov function, a signal compensation mechanism is constructed, and an adaptive law is designed to estimate unknown fault parameters, thereby reducing the impact of sensor failure faults on tracking performance. The proposed control method can simultaneously compensate for actuator and sensor faults, ensuring that the tracking error converges to a small neighborhood near the origin within a finite time, thereby improving the stability and safety of the system. Simulation results validate the effectiveness of this control method.